Pengaruh Etika, Perilaku Kerja dan Kepribadian terhadap Kinerja Pegawai pada Badan Pusat Statistik Kabupaten Pandeglang - Galih Suherman; M. Iqbal; Nisa Agustina (E-Journal Studia Manajemen, 2022)
In an era where the world has been formatted into a digital world or 4.0 in various sectors, quality human resources are needed. however, with employees who work not according to operational and management standards which results in decreased trust from the community. In 2017-2020 there are still employees' work ethics that do not have full integrity, work behavior is still not standardized, some employees work differently from what they should when collecting data. Given that there are still problems, the authors are interested in seeing how employee performance. This research was conducted to test and prove empirically the effect of Work Ethics, Work Behavior and Personality on Employee Performance. This research is a quantitative causal survey method using path analysis techniques. The survey method was used by giving a questionnaire to all employees as many as 60 people. The method used in this study is a qualitative descriptive research method that can describe employee performance. Data is presented in the form of descriptive data and is used by using the SPPS application version 2.1. Based on the research results, there is a positive and significant influence of Work Ethics on Employee Performance. There is a positive and significant influence on Work Behavior on Employee Performance. there is a positive and significant influence of personality on employee performance. There is a positive and significant influence on Work Ethics, Work Behavior, and Personality simultaneously on Employee Performance which is acceptable.